Regional Climates - Amador Astúa, Jorge Alberto (2021)
Regional Climates is one chapter from the State of the Climate in 2021 annual report. Compiled by NOAA’s National Centers for Environmental Information, State of the Climate in 2021 is based on contributions from scientists from around the world. It provides a detailed update on global climate indicators, notable weather events, and other data collected by environmental monitoring stations and instruments located on land, water, ice, and in space.